Finger force vectors in multi-finger prehension - Zatsiorsky, Vladimir M. (2003)
In a majority of studies on grasp, only normal forces were measured and only when a zero torque was exerted on a hand-held object. This study concerns finger force vectors during the torque production tasks. Subjects (n = 8) stabilized a handle with an attachment that allowed for change of external torque from −1.5 to 1.5Nm. Forces and moments exerted by the digit tips on the object were recorded. At the large (>−0.375Nm) supination torques the index/middle and ring/little pairs of fingers generated oppositely directed tangential forces. The index and middle finger produced forces in a downward direction and therefore did not support the load. At a zero torque and pronation torques, the middle, ring and little fingers produced forces along nearly the same direction. The vector of the index finger force was always directed differently from the vectors of other finger forces, the angles ranged from 19°30′ to 47°40′. The points of force application were systematically displaced with the torque, with the exception of the little finger. Tangential finger forces contributed substantially to the total torque exerted on the hand-held object.